IoT Edge Solutions for Cognitive Buildings - Cicirelli, Franco; Guerrieri, Antonio; Vinci, Andrea; Spezzano, Giandomenico (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book outlines the promise of the field of the Cognitive Internet of Things when it is applied to cognitive buildings. After an introduction, the authors discuss the goals of cognitive buildings such as operation in a more efficient, flexible, interactive, intuitive, and sustainable way. They go on to outline the benefits that these technologies promise to building owners, occupants, and their environments that range from reducing energy consumption and carbon footprint to promoting health, well-being, and productivity. The authors outline technologies that provide buildings and equipment with the ability to collect, aggregate, and analyze data and how this information can be collected by sensors and related to internal conditions and settings, energy consumption, user requests, and preferences to maintain comfort and save energy. This book is of interest to practitioners, researchers, students, and professors in IoT and smart cities.
Chapter 1. COGITO: a platform for developing cognitive environments -- Chapter 2. CLOUD, FOG and EDGE COMPUTING for IoT-ENABLED COGNITIVE BUILDINGS -- Chapter 3. Edge caching in IoT smart environments: benefits, challenges and research perspectives towards 6G -- Chapter 4. Needs analysis, protection, and regulation of the rights of individuals and communities for urban and residential comfort in Cognitive Buildings -- Chapter 5. Real case studies towards IoT Based Cognitive Environments -- Chapter 6. Audio analysis for enhancing security in cognitive environments through AI on the Edge -- Chapter 7. Aggregate Programming for customized building management and users preference implementation -- Chapter 8. IoT control based solar shadings: advanced operating strategy to optimize energy savings and visual comfort -- Chapter 9. Room occupancy prediction leveraging LSTM - An approach for cognitive and self-adapting buildings -- Chapter 10. Edge Intelligence against COVID-19: a Smart University Campus case study -- Chapter 11. Structural Health Monitoring in Cognitive Buildings -- Chapter 12. Development of Indoor Smart Environments leveraging the Internet of Things and Artificial Intelligence: a case study -- Chapter 13. Human-centered Reinforcement Learning for Lighting and Blind Control in Cognitive Buildings -- Chapter 14. Intelligent Load Scheduling in Cognitive Buildings: A Use Case -- Chapter 15. Cognitive Systems for Energy Efficiency and Thermal Comfort in Smart Buildings.
Keywords: Cooperating objects (Computer systems).; Telecommunication; Application software; Cyber-Physical Systems; Communications Engineering, Networks; Computer and Information Systems Applications